Типові слідчі ситуації під час збуту наркотичних засобів, психотропних речовин, їх аналогів або прекурсорів за допомогою мережі Інтернету - Мітякін, В. А.; Mitiakin, V. A. (Юридична наука. - 2020. - № 9 (111). - С. 151-156, 2020)
Розглянуто типові слідчі ситуації під час збуту наркотичних засобів, психотропних речовин, їх аналогів або прекурсорів за допомогою мережі Інтернету. Наголошено, що успішність розкриття та розслідування кримінального правопорушення будь-якого злочину залежить від правильного професійного процесуального оформлення його початку та ефективність досудового розслідування незаконного збуту наркотичних засобів, психотропних речовин, їх аналогів або прекурсорів за допомогою мережі Інтернету напряму залежить від обрання правильної лінії поведінки слідчим, прокурором одразу з моменту початку такого розслідування.

The article considers typical investigative situations during the sale of narcotic drugs, psychotropic substances, their analogues or precursors via the Internet. It is emphasized that the success of detecting and investigating a criminal offense of any crime depends on the proper professional procedural design of its beginning and the effectiveness of pre-trial investigation of illicit trafficking in narcotic drugs, psychotropic substances, their analogues or precursors directly depends on choosing the right course of action. the prosecutor immediately from the beginning of such an investigation. It is noted that the initial stage begins from the moment of receiving information about the criminal offense by the pre-trial investigation or the prosecutor, entering them into the ERDR and conducting all possible investigative (research) and covert investigative (research) actions to identify the criminal (persons) them) on suspicion. The next stage includes notification of the person of suspicion, application of measures to ensure criminal proceedings, in particular, precautionary measures, interrogation of him as a suspect and execution of all possible investigative (investigative) and covert investigative (research) actions in criminal proceedings aimed at forming evidence . The final stage includes resolving the issue of changing the suspicion and preparing for the opening of criminal proceedings, their opening, collection of data on the suspect, as well as the drafting of an indictment (petition for coercive measures of educational or medical nature, petition for release from criminal responsibility). It is emphasized that during the formation of typical investigative situations of the initial stage of the investigation of criminal proceedings on the sale of drugs, psychotropic substances, their analogues or precursors via the Internet, we can say that at the initial stage of the investigation will always be qualified under Art. 307 of the Criminal Code of Ukraine.

Рассмотрены типовые следственные ситуации при сбыте наркотических средств, психотропных веществ, их аналогов или прекурсоров посредством сети Интернет. Отмечено, что успешность раскрытия и расследования уголовного правонарушения любого преступления зависит от правильного профессионального процессуального оформления его начала и эффективность досудебного расследования незаконного сбыта наркотических средств, психотропных веществ, их аналогов или прекурсоров посредством сети Интернет напрямую зависит от правильной линии поведения следователям. прокурором с момента начала такого расследования.
Typical investigative situations during the sale of narcotic drugs, psychotropic substances, their analogues or precursors via the Internet
Мітякін, В. А. Типові слідчі ситуації під час збуту наркотичних засобів, психотропних речовин, їх аналогів або прекурсорів за допомогою мережі Інтернету / Мітякін В. А. // Юридична наука. - 2020. - № 9 (111). - С. 151-156. - DOI: https://doi.org/10.32844/10.32844/2222-5374-2020-111-9.18.
Мітякін , В. А. (2020). ТИПОВІ СЛІДЧІ СИТУАЦІЇ ПІД ЧАС ЗБУТУ НАРКОТИЧНИХ ЗАСОБІВ, ПСИХОТРОПНИХ РЕЧОВИН, ЇХ АНАЛОГІВ АБО ПРЕКУРСОРІВ ЗА ДОПОМОГОЮ МЕРЕЖІ ІНТЕРНЕТУ. Юридична наука, (9 (111), 151–156. https://doi.org/10.32844/10.32844/2222-5374-2020-111-9.18.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; типові слідчі ситуації; typical investigative situations; типичные следственные ситуации; незаконний збут; illegal sale; незаконный сбыт; наркотичні засоби; narcotics; наркотические средства; психотропні речовини; psychotropic substances; психотропные вещества; Інтернет; Internet; Интернет